Scapular fracture: lower severity and mortality - Salim, Javad; Khaji, Ali; Karbakhsh, Mojgan; Saadat, Soheil; Eftekhar, Behzad (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The presence of scapular fracture is believed to be associated with high rates of other injuries and accompanying morbidities. The aim was to study injury patterns and their overall outcomes in patients with scapula fractures. DESIGN AND SETTING: Cross-sectional study of trauma patients treated at six general hospitals in Tehran. METHODS: One-year trauma records were obtained from six general hospitals Among these, forty-one had sustained a scapular fracture and were included in this study. RESULTS: Scapular fracture occurred predominantly among 20 to 50-year-old patients (78%). Road traffi c accidents (RTAs) were the main cause of injury (73.2%; 30/41). Pedestrians accounted for 46.7% (14/30) of the injuries due to RTAs. Falls were the next most common cause, accounting for seven cases (17.1%). Body fractures were the most common type of scapular fractures (80%). Eighteen patients (43.9%) had isolated scapular fractures. Limb fracture was the most common associated injury, detected in 18 cases (43.9%). Three patients (7.3%) had severe injuries (injury severity score, ISS ≥ 16) which resulted in one death (2.4%). The majority of the patients were treated conservatively (87.8%). CONCLUSIONS: Patients with scapula fractures have more severe underlying chest injuries and clavicle fractures. However, this did not correlate with higher rates of injury severity score, intensive care unit admission or mortality.